Conceptual Feminist Utopia and Literary Discourse: Two Novels by Roxana Pinto - Bonilla Navarro, José Francisco (2018)
An analysis of the literary representation of feminine models in two of Roxana Pinto’s novels, is carried out from the perspective of the theoretical and methodological paradigm which views the feminist position as a process in construction, in which contradictions and respect for difference can be included as components of their own ontological construction. Mention is made of the concept of non-dialectic heterogeneities, a concept which reafirms the complexity of the feminine models presented in the texts. The article emphasizes that most models of feminineness are contradictory and complex.